Repercussões do pacto nacional pela alfabetização na idade certa (PNAIC) na formação e prática pedagógicada educação matemática no ciclo de alfabetização - Sousa, Vanda Maria de (2018)
This research studies the impacts of the National Pact for Literacy at the Right Age (PNAIC, in the Portuguese acronym) on Math teachers´ practice from the Municipal Education Network of Curitiba. The Municipal Secretary of Education of Curitiba offers continuing education courses to all teachers under its responsibility. Nevertheless, based on internal assessment carried out by the Municipal Secretary of Education and by the Prova Brasil it is possible to observe the need to improve students´ mathematical knowledge. In 2014, PNAIC was offered to all the Math teachers responsible for literacy from the mainstream municipal schools; the program discussed not only teaching, but also the education of literacy teachers. Taking this into consideration, the aim of this research is to analyze the impacts of the formative aspects of the PNAIC on the Mathematical Education practice in the context of public policies for continuing education of literacy teachers. The specific aims of the study are to investigate the public policies for continuing education of literacy teachers and highlight PNAIC as a program that involves Mathematical Education; understand Mathematical Education in the educational literature and in the guidelines for the teaching of Math at the national, state and municipal levels; analyze the impacts of the PNAIC– Math – on the continuing education and practice of teachers from the Mainstream Municipal Schools. The research has a qualitative approach and based its data collection on documental, empirical data and on their interpretations. The analysis was dialectical from a historical materialistic perspective with the aim of observing the social, political and economic determinants in addition to the contradictions that are part of the reality of continuing education of PNAIC and the Mathematical Education practice at mainstream municipal schools in Curitiba. Studies that have similar aims were selected at the dissertation and theses Capes database; these studies, pointed out criticism to the implementation of the policy as well as contributions to the practice of literacy teachers. These studies demonstratethat the PNAIC provided teachers the opportunity to reflect, share experiences and the possibility to give new meaning to their practice in the construction of Mathematical concepts. Few studies investigated the contents of Mathematical Education. The research also discussed the fast provision of continuing education in terms of the contents of the program and the competence of teacher trainers who in general are not specialists in the area. The analysis of the interviews carried out with 8 teachers from mainstream municipal schools, demonstrate that they recognize the contributions of the PNAIC to their practice. This outcome is similar to the outcomes of most research presented in the literature review. The program enriched teachers´ practice, brought back playful activities, provided suggestions of materials for Mathematical literacy as well as a bibliographical collection. The investigation also pointed out some problems: the non-use of the course provisions, as the mainstream municipal secretary of education set other functions to these professionals, and the short time to learn the contents of the courses, which were considered dense. It also pointed out the importance of follow up and assessment of the program to consider the positive aspects as well as the mistakes in the implementation. Finally, this study found in the interviews meaningful contributions and aspects that indicate the need to carry out more investigations.